The evolutionary and creationist conceptions in the education of undergraduate students of Biological Sciences (Research, Society and Development, 2021)
The Theory of Evolution today maintains the status of a unifying theory and benchmark of biological studies and concepts, and its importance is evident in the curricular parameters currently established. However, evolutionary science often faces a resistance, most often, by religious entities, especially those of the Christian aspect. The area of education resents this trend, and to better understand it impacts this work conducted a research with undergraduate students of Biological Sciences, in order to verify the possibility of interference of the religious experiences of the interviewees, with the acceptance or assimilation of the content of the disciplines and the evolutive concepts. In addition, it was necessary was to verify the level of knowledge of these students on some evolutionary mechanisms and concepts, as well as conceptual errors commonly made by students. The results obtained firm, in part, with the studies mentioned in this work, identifying those different religious experiences of students of the Biological Sciences course can interfere in their evolutionary conceptions and, in the medium term, when assuming the role of Biology and Science teachers, affect their future teaching-learning relationships with their students.